Forceful patterning: theoretical principles of mechanochemical pattern formation - Rombouts, Jan; Elliott, Jenna; Erzberger, Anna (EMBO reports, 2023)
Biological pattern formation is essential for generating and maintaining spatial structures from the scale of a single cell to tissues and even collections of organisms. Besides biochemical interactions, there is an important role for mechanical and geometrical features in the generation of patterns. We review the theoretical principles underlying different types of mechanochemical pattern formation across spatial scales and levels of biological organization.
Gesehen am 18.12.2023